2006
DOI: 10.1177/0269881107077351
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological manipulations of arousal and memory for emotional material: effects of a single dose of methylphenidate or lorazepam

Abstract: Benzodiazepines produce robust impairments of memory alongside global decreases in physiological and subjective arousal. Recently one benzodiazepine (triazolam) has been found to disproportionately impair memory for emotionally arousing material (Buchanan et al., 2003). The extent to which this effect may be mediated by the drug's sedative action is unclear. The present study aimed to assess how pharmacologically decreasing physiological arousal with a benzodiazepine and increasing arousal with a stimulant imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 61 publications
(93 reference statements)
1
19
0
Order By: Relevance
“…Despite producing opposite effects on sleepiness, both lorazepam and methylphenidate reduce the impact of emotionally arousing aversive material on memory, indicating a dissociation between drug effects on aversive memory and drug effects on sleepiness (32). Furthermore, a study with the sedative lorazepam found drug-induced memory impairments independent of emotional valence (33).…”
Section: Resultsmentioning
confidence: 97%
“…Despite producing opposite effects on sleepiness, both lorazepam and methylphenidate reduce the impact of emotionally arousing aversive material on memory, indicating a dissociation between drug effects on aversive memory and drug effects on sleepiness (32). Furthermore, a study with the sedative lorazepam found drug-induced memory impairments independent of emotional valence (33).…”
Section: Resultsmentioning
confidence: 97%
“…While there is evidence that MPH can improve declarative memory [43] and cognitive control [44] in college students, it is important to note that nonmedical users tend to have lower grade point averages [45], calling into question the long term success of such use. Regardless, the results presented here seem to be consistent with findings that MPH exposure can improve learning performance under specific circumstances even when administered in late adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have found that benzodiazepines have the ability to impair functions related to amygdala activity including fear conditioning [184][185][186], recognition of fearful emotional faces [187], and memory for emotional stimuli relative to neutral stimuli [188,189].…”
Section: Human Imaging Studies: Effects Of Anxiolytics On Amygdala Acmentioning
confidence: 99%
“…As discussed in the human studies in Section 4.1 above [184,188,189], a key aspect of benzodiazepine action may be the ability to modulate emotional memory. Here the BLA once again appears to be a main site of benzodiazepine action.…”
Section: Evidence Delineating Effects Of Anxiolytic Drugs On Amygdalamentioning
confidence: 99%